1990
DOI: 10.1017/s0950268800047646
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid profile analysis and antimicrobial susceptibility patterns of shigella isolates from Nigeria

Abstract: SUMMARYIn an epidemiological survey, plasmid profiles and antimicrobial susceptibility testing of 100 shigella isolates in Lagos, Nigeria was done. All the isolates were sensitive to nalidixic acid, nitrofurantoin and ciprofloxacin. The commonest antimicrobial susceptibility pattern was resistance to ampicillin, colistin sulphate, co-trimoxazole, streptomycin and tetracycline. All but 4 of 100 isolates screened contained one or more plasmids. Plasmid profile analysis distinguished more strains than did antimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
20
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 14 publications
12
20
0
Order By: Relevance
“…Drug susceptibility of Salmonella and Shigella isolates showed that they were resistant to ampicillin, which is in agreement with the findings of other researchers in Nigeria [25], [26] and also in agreement with studies done in Kenya [27] and in Uganda [28]. In this study, Salmonella and Shigella were sensitive to the following antibiotics: ceftriaxone, gentamycin, ciprofloxacin, chloramphenicol, and nitrofurantoin.…”
Section: Discussionsupporting
confidence: 93%
“…Drug susceptibility of Salmonella and Shigella isolates showed that they were resistant to ampicillin, which is in agreement with the findings of other researchers in Nigeria [25], [26] and also in agreement with studies done in Kenya [27] and in Uganda [28]. In this study, Salmonella and Shigella were sensitive to the following antibiotics: ceftriaxone, gentamycin, ciprofloxacin, chloramphenicol, and nitrofurantoin.…”
Section: Discussionsupporting
confidence: 93%
“…Representative profiles of plasmids of each of the four serogroups are presented in Figures 1-4. DISCUSSION The shigellae continue to be important aetiological agents of dysentery gastroenteritis in India [1,11,12], the United States [13], Nigeria [2], Australia [3], Vellore [14] and Bangladesh [15]. This is also true for Taiwan [4,10].…”
Section: Resultsmentioning
confidence: 99%
“…Shigellosis is one of the most prevalent and important diseases in the developing countries [1][2][3], and is the major cause of dysentery in Taiwan [4]. Resistance of Shigella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmid profile analysis could differentiate these selected isolates. This may reflect the presence of a large number of different endemic isolates or a high rate of plasmid transfer amongst isolates or both (Olukoya and Oni, 1990). The diverse patterns of plasmid profiles observed among isolates in the current study could be also due to higher exposure of people to enteric bacteria in these places with poor sanitation (Olukoya and Oni, 1990).…”
Section: Plasmid Profile Analysis-based Characterization Of Mdr Isolatesmentioning
confidence: 74%